(untitled) (Pubmet, 2022)
Even though open access to scholarly works is globally recognized as a goal to be achieved as soon as possible, it is far clearer how to achieve this for journals than for books. Even organizations firmly oriented towards open access to all results of publicly funded research, such as Coalition S, acknowledge the complexity of book publishing and recognize that open access to books will require more complex models of realization over a longer period (COAlition S Statement on Open Access for Academic Books, 2021). In recent years, the academic community has recognised the central role of books in scholarly communication in social sciences and humanities (SSH) and intensified discussions about possible roads to open access, especially within organizations such as OPERAS (Stone et al., 2021), Science Europe (Briefing Paper on Open Access to Academic Books, 2019), SPARC Europe or Open Access Book Network (A Plan S for Books?, 2021). These documents and discussions portray European book publishing as a fragmented space, with many smaller nationally oriented markets in which there is no domination of large publishers. It is clear that the models of transition to open access will not be unique for the whole European area. Diverse mechanisms and sustainable business models will be appropriate to different contexts. In considering the most appropriate models of transition, an accurate and detailed insight into individual national and regional specifics can be of great importance. The aim of this research is to show the current state of scholarly book publishing in SSH in Croatia: who are the key stakeholders, what are their characteristics, and what is the current level of open access to scholarly books? To answer these questions we rely on data from two different sources. The main source of funding to cover the costs of scholarly book publishing in Croatia are the direct subsidies from the Ministry of Science and Education. Given that data on grant recipients are publicly available, it is possible to see what types of books are being published by what types of publishers (research performing institutions, small and medium-sized enterprises, scholarly societies, and other types of organizations). The analysis will be based on data from 2018 to 2021 and will also use the insights from an earlier analysis of the same funding scheme by F. Horvat and Z. Velagić (2020). The second source is the Croatian Scientific Bibliography (CROSBI), and our review will include data on SSH books (monographs and edited books) published over the same period (2018–2021). CROSBI provides information about active book publishers in Croatia, but also about e-editions, especially those in open access. Particularly useful is the information about OA books on publisher platforms (“gold” model) and in open repositories (“green” model), which gives an insight into preferred OA models for different types of publishers. In addition, publisher platforms provide info about standards used in digital publishing (quality assurance, standardized metadata and discoverability, licensing, indexing, and preservation). These two sources give us a pretty accurate idea of the current state of SSH book publishing in Croatia and a good starting point for creating a national open science plan for book publishing.